2006
DOI: 10.1080/01926230601072327
|View full text |Cite
|
Sign up to set email alerts
|

Urothelial Carcinogenesis in the Urinary Bladder of Male Rats Treated with Muraglitazar, a PPARα/γ Agonist: Evidence for Urolithiasis as the Inciting Event in the Mode of Action

Abstract: Muraglitazar, a PPARα/γ agonist, dose-dependently increased urinary bladder tumors in male Harlan Sprague-Dawley (HSD) rats administered 5, 30, or 50 mg/kg/day for up to 2 years. To determine the mode of tumor development, male HSD rats were treated daily for up to 21 months at doses of 0, 1, or 50 mg/kg while being fed either a normal or 1% NH 4 Cl-acidified diet. Muraglitazar-associated, time-dependent changes in urine composition, urothelial mitogenesis and apoptosis, and urothelial morphology were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 77 publications
1
71
0
Order By: Relevance
“…In this setting, the combined agonists at pharmacologic concentrations result in bladder and/or kidney carcinogenesis with at least five dual agonists (10). One detailed pathologic study provides evidence that chronic effects of urolithiasis contribute to this effect (65). This has resulted in withdrawal of most of these agents from further testing.…”
Section: Clinical-translational Advancesmentioning
confidence: 99%
“…In this setting, the combined agonists at pharmacologic concentrations result in bladder and/or kidney carcinogenesis with at least five dual agonists (10). One detailed pathologic study provides evidence that chronic effects of urolithiasis contribute to this effect (65). This has resulted in withdrawal of most of these agents from further testing.…”
Section: Clinical-translational Advancesmentioning
confidence: 99%
“…Dual-acting "-glitazars" appear more potent than PPARγ agonists at inducing tumors associated with the lower urinary tract (LUT) in rats. Some studies suggested an indirect effect, in which bladder cancer resulted from regenerative responses to damage induced by precipitated urinary deposits in male rats (Cohen, 2005;Dominick et al, 2006;Tannehill-Gregg et al, 2007). However, others have suggested a direct effect of PPAR agonists on the rat bladder epithelial (urothelial) lining, based on rapid changes in urothelial gene expression and intracellular signaling, as well as early urothelial hypertrophy in treated rats (Egerod et al, 2005;Oleksiewicz et al, 2005).…”
mentioning
confidence: 99%
“…It is therefore essential that the urine is collected from nonfasted animals at appropriate times during the day to reflect the various compositions of urine over a 24-hour period (Dominick et al, 2006). For most purposes, this requires fresh void urine collected either at night or shortly after the lights go on in the morning.…”
Section: Introductionmentioning
confidence: 99%